STORYTELLING FOR LITERATURE STUDENTS: NARRATIVE INNOVATION IN BUSINESS MODEL DESIGN - Nur Asiyah; Wildi Adila; Muhammad Rizal; Arya Saputra; Irawan Irawan (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
Storytelling is a strategic tool that conveys meaning in literature and evokes emotional depth, cultural insight, and imaginative expression. In addition, storytelling also drives innovation in various fields such as business and entrepreneurship. However, many students of English literature are unaware that their strengths in narrative thinking can be developed into valuable entrepreneurial skills. This study addresses that gap by designing a storytelling-based Business Model Canvas (BMC) as a learning tool for the Literature and Entrepreneurship course. This study uses Fisher's Narrative Paradigm Theory, which explains Human beings as natural storytellers. Besides, it is supported by Osterwalder's BMC framework. Using a Research and Development (R&D) method adapted from Branch ADDIE, the research produced digital instructional media in the form of videos and an application designed through Canvanizer, Google Sites, and Kodular. These platforms were used to embed narrative thinking into each component of the BMC. The content expert and IT validate the Product. It was tested in a small and a large group trial. Findings show that integrating storytelling into the business modelling process significantly strengthens students' ability to construct and communicate ideas, especially aligning their creativity with practical entrepreneurial thinking. The final product was found to be pedagogically feasible and relevant, contributing to the development of literature students as creative digitalpreneurs. It concludes that narrative approaches can be effectively adapted to entrepreneurship education in the humanities. Therefore, further research suggested exploring cross-disciplinary applications of the model for the long-term impact.